Deteksi Dini Kejadian Hipotermia dengan Pemberian Penyuluhan Kesehatan pada Pasien Pasca Anestesi Spinal - M. Rossy Rachasiwi; Naufal Annasy (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Hypothermia is a common complication following spinal anesthesia, which can lead to more severe consequences if not detected and treated early. Early detection of hypothermia is essential for preventing additional complications, such as cardiovascular instability, delayed recovery, or prolonged hospitalization. This study aims to analyze the effectiveness of providing health education in improving the early detection of hypothermia among patients after spinal anesthesia at Gemolong Regional Hospital. The research utilized a quantitative approach, applying a pre-experimental one-group pre-test and post-test design to measure the impact of the intervention. A total of 15 patients who underwent spinal anesthesia were selected as respondents and were provided with health education on recognizing the signs, risks, prevention, and treatment of hypothermia. Health education sessions were conducted through interactive presentations and written materials, emphasizing practical knowledge that could be directly applied by healthcare staff and patients. The primary data collection tool involved pre-test and post-test assessments to measure the participants' understanding of hypothermia and its management. The results indicated a significant improvement in the patients' understanding of hypothermia after receiving the health education. The average score of the post-test was noticeably higher than the pre-test, suggesting that the education effectively increased awareness and preparedness for early detection of hypothermia. This finding emphasizes the importance of integrating health education programs into clinical practice, especially for patients undergoing spinal anesthesia, to enhance early detection and reduce the risks of complications related to hypothermia.